2017
DOI: 10.1142/s0217984917400322
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of heterogeneous deformation measurement in digital image correlation

Abstract: Heterogeneous deformation measurement using traditional digital image correlation (DIC) has times error of homogeneous deformation due to localized complexity. In case of small strain window, displacement field error will substantially corrupt the derived strain. On the contrary, large strain window will induce a reasonable information reduction in particular of heterogeneous deformation. In this paper, a novel parameter was put forward to correct displacement field and select strain subset size dynamically. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Zhao et al [5] established a 14-DOF vehicle model, then studied the coordinated control among active suspension system (ASS), AFS and DYC and found that the method could effectively improve the lateral and longitudinal dynamics of vehicles. Shen et al [6] combined four-wheel steering (4WS) with DYC to ensure vehicle stability by generating appropriate 4WS angle and correcting yaw moment based on sliding mode control and verified the effectiveness of the method through experiments. In this study, an integrated control method combining ARS with DYC was designed for 4WID to improve the control effect when the tyre was in the non-linear state.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [5] established a 14-DOF vehicle model, then studied the coordinated control among active suspension system (ASS), AFS and DYC and found that the method could effectively improve the lateral and longitudinal dynamics of vehicles. Shen et al [6] combined four-wheel steering (4WS) with DYC to ensure vehicle stability by generating appropriate 4WS angle and correcting yaw moment based on sliding mode control and verified the effectiveness of the method through experiments. In this study, an integrated control method combining ARS with DYC was designed for 4WID to improve the control effect when the tyre was in the non-linear state.…”
Section: Introductionmentioning
confidence: 99%